2017
DOI: 10.1073/pnas.1618239114
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell migration and mechanotransduction on linear stiffness gradient hydrogels

Abstract: The spatial presentation of mechanical information is a key parameter for cell behavior. We have developed a method of polymerization control in which the differential diffusion distance of unreacted cross-linker and monomer into a prepolymerized hydrogel sink results in a tunable stiffness gradient at the cell-matrix interface. This simple, low-cost, robust method was used to produce polyacrylamide hydrogels with stiffness gradients of 0.5, 1.7, 2.9, 4.5, 6.8, and 8.2 kPa/mm, spanning the in vivo physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
323
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 410 publications
(353 citation statements)
references
References 68 publications
13
323
3
1
Order By: Relevance
“…Expression changes in mechanosensitive proteins verified typical ASC mechanotransduction occurring in response to ECM stiffness. Increased nuclear localization of YAP was observed on stiffer hydrogels (Figure b) in agreement with previous findings (Dupont et al, ; Hadden et al, ; Swift et al, ), and MRTF‐A followed the same trend (Figure b; p < 0.05) as expected from previous findings (Shiwen et al, ).…”
Section: Resultssupporting
confidence: 92%
“…Expression changes in mechanosensitive proteins verified typical ASC mechanotransduction occurring in response to ECM stiffness. Increased nuclear localization of YAP was observed on stiffer hydrogels (Figure b) in agreement with previous findings (Dupont et al, ; Hadden et al, ; Swift et al, ), and MRTF‐A followed the same trend (Figure b; p < 0.05) as expected from previous findings (Shiwen et al, ).…”
Section: Resultssupporting
confidence: 92%
“…Durotaxis is a class of externally directed cell migration in which the direction of cell migration is governed by a local physical parameter: the stiffness of the migratory substrate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Durotaxis has been characterized in detail recently in several nonmalignant cell types, generally those derived from a mesenchymal lineage (e.g., see (48,49)). However, it was not clear whether cancer cells can also undergo effective durotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques, including photochemical reactions with spatially controlled UV irradiation (Nemir, Hayenga, & West, ; Norris, Tseng, & Kasko, ; O'Connell et al, ; Sunyer, Jin, Nossal, & Sackett, ; Wong, Velasco, Rajagopalan, & Pham, ), physical crosslinking (Kim et al, ; Oh, An, Kim, & Lee, ), and diffusion‐based crosslinking (Hadden et al, ; Hartman, Isenberg, Chua, & Wong, ; Lee et al, ), have been suggested to realize the stiffness gradient platforms. The approaches were generally based on synthetic polymers or chemically modified natural polymers as substrate material, including polydimethylsiloxane (Wang, Tsai, & Voelcker, ), polyacrylamide (Hadden et al, ; Hopp et al, ; Sunyer et al, ), polyvinyl alcohol (Kim, An, et al, ; Oh et al, ), and gelatin (O'Connell et al, ). The stiffness gradient platforms enabled high‐throughput examinations of stiffness effect on various cellular responses in a certain range of the stiffness on a single substrate (Hopp et al, ; Kim, An, et al, ; Oh et al, ; Wang, Tsai, & Voelcker, ).…”
Section: Introductionmentioning
confidence: 99%